Sorção e migração de biodiesel em um latossolo argiloso - Cecchin, Iziquiel (2014)
Because of accelerated industrial growth that has been unleashing on the world stage, the environmental impacts associated with these inevitably end up increasing at the same scale. In this respect, accidents involving spills of oily compounds has been the subject of numerous studies, challenging the professionals who work in the area. This study aimed to evaluate how physicochemical and structural factors of a clay soil can influence the sorption and migration of a spill of soybean biodiesel. The soil samples were collected at 1.2 m depth in a trench in the experimental campus of the University of Passo Fundo. Was realized tests of physical and chemical classification of the studied soil, which is classified as a Dystrophic Humic Red Latosol with low organic matter content. The experimental procedure was performed in three steps. For the determination of the characteristic curves, was molded up samples of 100 g of dry soil in 15 different moisture contents ranging from 15 to 36 and void ratios of 1.14, 1.24 and 1.34, being carried out one experimental block without addition of nutrients and another block with the presence of these. For the isolation of the adsorption variable, was molded up samples of 100 g of dry soil at different void ratios (1.14, 1.24 and, 1.34), different moisture content (15, 25 and 35%), being carried out one experimental block without addition of nutrients and another block with the presence of these. In both experimental blocks, it was mixed with the soil mass during the molding step an amount equivalent to a biodiesel contamination of 40 g/kg of dry soil (4%). After molded, the samples were stored and sterilized being defined 3 contact time between the soil and the contaminant: 0, 15 and 30 days. For the evaluation of the influence of the rainfall, the samples was molded using 400 grams of dry soil at different void ratios and different moisture content with and without the addition of nutrients. The samples were submitted to a simulated spill equivalent to the volume of voids of each specimen being left in the percolation of this for a period of 15 days. After this period, the samples were subjected to three simulated rainfall values (0, 30, 60 mm) and left to stand for this percolating for a period of 15 days. The residual content were performed quantitatively by the ultrasound method, determining the residual saturation of the contaminant. The characteristic suction curves obtained indicated that the addition of nutrients in the samples, increase significantly the suction in the soil. In the experiments of isolation of adsorption, the results showed that the moisture content had a large influence in the experiment, providing in the samples with 15% moisture a reduction of the contamination up to 54% greater than that obtained in specimens with 35% of moisture. The presence of nutrients provided a reduction in the sorption capacity in practically all structural configurations studied. Was observed that the greatest results of residual contaminant content occurred in the specimens with 15% of moisture and no rainfall simulation. The effects of simulated rainfall was presented one of the most influential factors for the specimens with the addition of nutrients, promoting greater reductions than in specimens without the addition of these. Moisture also presented itself as a great influencing factor in the experiment, being that the samples with lower moisture had higher contaminant extracted results. We conclude that the application of biostimulation with chemical nutrients promote the increase of the plume of contamination of biodiesel, being necessary to consider this factor before decide start and intervention in the impacted area